Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


To more easy to understand why it comes up 3x(x-2)
3x1 = 3
3x2 = 6
so both 3 and 6 is had a factor of 3
3x^2 = 3 times x times x =  3x(x)
-6x =  3 times 2 times x = 3x(2)
then the equation becomes
3x(x)-3x(2) =
3x is common to both terms
so you can put it outside of the terms and put parentheses to know that it is to be multiply
like this : 3x(x-2)

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts